A Comparison of UK versus European guidelines in neuro-urology. (March 2018) - Ecclestone, Hazel; Hamid, Rizwan
Two primary guidelines, written by the European Association of Urology (EAU) and National Institute of Clinical Excellence (NICE), have been designed to aid British urologists with managing neuro-urological patients. The EAU guidelines are updated annually, and cover incontinence, sexual function and infertility in the adult neuropathic population. The NICE guidelines, applicable to England, are periodically updated, with the last update being in 2012. The NICE guideline covers adults and children with neurological incontinence. There are fundamental differences in the recommendations of the panels. EAU advocate upfront urodynamics and ultrasound assessment in all patients and treatment recommendations are based on urodynamic findings rather than patient symptoms on which the NICE guidelines are based. The patient group covered comprises a heterogeneous population, including patients at high risk of renal deterioration without urological intervention. Due to this, both guidelines recommend initial risk stratification to determine assessment and follow-up regimens. The reason for variation may be due to the NICE guidelines having an added dimension, in that they ensure all interventions are cost effective for a publicly funded national health service. Both guideline panels acknowledge the paucity of scientific research in the field of neuro-urology and consequently both guidelines are based upon expert opinion and limited retrospective evidence. There is an urgent need to undertake prospective research in this field. A first step can be an establishment of prospective registries among various neuro-urological units.